Smartphones addiction and mental-emotional disorders among adolescents : A cross sectional study - Wijoyo, Eriyono Budi; Fadhilah, Rafiqah; Umara, Annisaa Fitrah (Universitas Muhammadiyah Yogyakarta, 2023)
Background: A smartphone is a communication tool designed to be used for a variety of applications. Excessive usage of smartphones can cause addiction, especially in adolescents. Because of this, adolescents can experience emotional-mental disorders caused by smartphone addiction.Objective: This study aimed to examine the relationship between smartphone addiction and emotional-mental disorders.Methods: This study had a quantitative research using a cross sectional study design. Smartphone addiction was measured using the Smartphone Addiction Scale-Short Version (SAS-SV) instrument, while mental emotional disorder was measured using the Self Reporting Questionnaire (SRQ) instrument.The sample size of this study was 103 adolescents. Samples were taken by simple random sampling and analyzed by chi-square.Results: The results of this study show that there is a relationship between smartphone addiction and emotional and mental disorders in adolescents with p-value 0.02.Conclusion: More support is needed from various parties to prevent adolescents from experiencing smartphone addictionand subsequently experiencing mental and emotional disorders.